2023
DOI: 10.3390/diagnostics13061049
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Robotic-Assisted Bronchoscopy in the Diagnostic Evaluation of Peripheral Pulmonary Lesions: A Paradigm Shift

Abstract: Despite recent developments, evaluation of peripheral pulmonary lesions (PPL) remains clinically challenging, and the diagnostic yield of many image-guided and bronchoscopy methods is still poor. Furthermore, complications from such procedures, such as pneumothorax and airway hemorrhage, are a major concern. Recently launched robotic-assisted bronchoscopy (RAB) platforms are still in the early exploration stage and may provide another tool for achieving PPL evaluation. We present our experience here as a retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A total of 26 studies were selected to review the full article. Of these, 16 studies were excluded: five studies did not report diagnostic results, 15 , 16 , 17 , 18 , 19 nine studies did not provide sufficient data to calculate the diagnostic yield according to our definition, 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 and two studies were excluded to avoid duplication of population. 29 , 30 Finally, 10 eligible studies with 725 lesions were included.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 26 studies were selected to review the full article. Of these, 16 studies were excluded: five studies did not report diagnostic results, 15 , 16 , 17 , 18 , 19 nine studies did not provide sufficient data to calculate the diagnostic yield according to our definition, 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 and two studies were excluded to avoid duplication of population. 29 , 30 Finally, 10 eligible studies with 725 lesions were included.…”
Section: Resultsmentioning
confidence: 99%
“…However, a comparative cohort study showed that ssRAB and Digital Tomosynthesis-Electromagnetic Navigation Bronchoscopy (DT-ENB) had comparable diagnostic yields and safety profiles [13]. These studies show the diagnostic yield of ssRAB for peripheral pulmonary lesions ranging from 77% to 86% [6‒10, 13‒15]. However, there is little information on diagnostic yield of ssRAB for pure GGNs or SSNs specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that using ssRAB has a high diagnostic yield, ranging from 79% to 93.3% [6][7][8][9][10]. ssRAB has also shown an exceptional safety profile [6].…”
Section: Introductionmentioning
confidence: 99%
“…1). Component 1, the blue case with all the components inside, is reusable and houses two electric motors (3,4), specifically the Robotis Dynamixel AX 12A, along with the control boards (7), including the OpenCM9.04-C controller and the OpenCM845 expansion board (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%